Systematic review of literature: Advantages and challenges in implementing the Project-Based Learning (PjBL) - Wita Ferwati; Agus Junaidi; Efendi Napitupulu; Abdul Hamid (Institute of Computer Science (IOCS), 2023)
This research aims to explore the advantages and challenges of the Project Based Learning (PJBL) learning model in developing higher-order thinking skills among students. This research uses the Systematic Literature Review (SLR) method. This research analyzes search results originating from the Scopus, Erics, and Google Scholar databases, spanning the last 10 years. The limitation of this research is that the articles used consist of a period of 10 years. It is hoped that in future research the data can be further improved. Based on the article data that was searched, 10 articles were taken which were used as study material. The results of the analysis of the review of this article can draw conclusions and findings that the learning model (PjBL) has the following advantages: 1) can increase student motivation and involvement in the learning process, 2) develop real skills, 3) increase learning outcomes and collaboration and communication skills, critical thinking, and creative thinking; 4) active and student-centered learning. Meanwhile, the weaknesses of the Project Learning Model (PJBL) are: 1) implementing PjBL the teacher must prepare a project that will be used in learning so it requires a lot of time; 2) This PjBL requires complete facilities to be implemented well so several schools have limited resources; 3) in implementing PjBL, it is difficult to involve all students in group work because not all students are active; 4) the costs of implementing PjBL require a lot of money so the use of this PjBL learning model needs to be considered.